Lipid metabolism in the rumen - De Beni Arrigoni, Mário [UNESP]; Martins, Cyntia Ludovico [UNESP]; Factori, Marco Aurélio [UNESP] (Springer Nature, 2016)
The increase of energy concentration in rations formulated for ruminants has become an important topic while demands for increasing productivity grows, especially in finishing periods for beef cattle and sheep, and strategically for dairy cows, depending on the stage of lactation. Seeking for alternatives to excessive starch inclusions, several studies have been pointing out as potential solution the utilization of compounds that contain high-energy concentration, since its limitations are understood and its benefic properties maximized.